The Role of Parents in Educating Children in the Industrial Revolution Era 4.0 - Yuda Rudiana (STIT Islamic Village Tangerang, 2020)
Mini thesis, Islamic Education Department, July 2020. These research objectives held to know how the parent's concept of educating children in the industrial revolution era 4.0, in Kp. Undrus, Cijantra Village, Kab. Tangerang also to know the parents' obstacle factor on the process that educating children in the industrial revolution era 4,0, in Kp. Undrus, Cijantra Village, Kab. Tangerang. This research used a field study approach in Kp. Undrus, Cijantra Village, Kab. Tangerang. The technique's data collection in this research used observation, interview, and documentation. While the data analysis used data collection, data presentation, data reduction, and data verification or taken conclusion. Then, used a validity test technique with the prioritize as data credibility, data transferability, real power, also a confirmation research object. This research result indicates that the parent has an important role in preparing for the industrial revolution 4.0. Through education has done parents in a family by various ways as harmonization the relation of parent-child, became examples to children, motivate and support to the in learning, and have a clear purpose be parents in Kp. Undrus, Cijantra Village, Kab. Tangerang in educating children in the industrial revolution 4.0. children education by the parents have to deficient in economy providing media learning, lack of understanding matter learning child by the parents and lack of compliance to parents.